ANALISIS KUALITAS PENINGKATAN PELAYANAN MELALUI APLIKASI MOBILE JELAJAH KEBUN RAYA BOGOR - Ayang Risma Yulianita; Tiara Puspanidra; Ratih Siti Aminah (UNIVERSITAS PAKUAN, 2020)
Abstract Technology mobile application is utilized by the Bogor Botanical Gardens under Lembaga Ilmu Pengetahuan Indonesia (LIPI) as one of the attractions in the city of Bogor by designing an Android-based mobile application for visitors to the Bogor Botanical Gardens, called Jelajah Kebun Raya Bogor application. This research is a qualitative descriptive study using Kotler's theory of the quality dimensions of service delivery which includes physical evidence, empathy, reliability, quick response and assurance. The results of the research note that the application is designed to improve the quality of public services and to facilitate the visitors down the extent of the area of the Bogor Botanical Gardens. There are features on applications i.e., features information about the history of the plant and other historic buildings that are in the Bogor Botanical Garden to make it easy for visitors to get the information needed to facilitate navigation and features visitors exploring the vastness of the areas of the Bogor Botanical Gardens, content in the application is accurate and secure, in accordance with the needs of visitors, improve the renewal applications. Keywords: Service Improvement, Mobile Application, Jelajah Kebun Raya Bogor.